Ambidextrous Blockchain Governance to Strengthen BankCo’s Digital Transformation through COBIT 2019 Traditional and DevOps - Aisyah, Salsabill Nur; Mulyana, Rahmat; Kusumasari, Tien Fabrianti (Universitas Muhammadiyah Malang, 2025)
The adoption of blockchain in banking accelerates digital transformation by enhancing transparency and operational efficiency. However, it also brings with it governance issues pertaining to accountability, compliance, and system integrity within a highly regulated environment. This study addresses these challenges by developing a blockchain governance solution based on ambidextrous approach within COBIT 2019’s Traditional and DevOps Focus Areas. A governance model was built and evaluated through iterative steps. Until saturation was reached, information was gathered through key stakeholder interviews and checked with internal documentation such as yearly reports, risk frameworks, and policy records. The ambidextrous COBIT 2019 framework was used in the analysis for all seven governance components. Governance and Management Objectives (GMOs) were prioritized based on design factors, national regulations (POJK No.11/2022 and SOE Minister Regulation No.PER-2/MBU/03/2023), and insights from prior studies. APO12: Managed Risk was identified as the most prioritized GMO. A capability gap analysis revealed missing leadership roles, overlapping security responsibilities, and underdeveloped risk management practices. Recommendations include formalizing key governance roles and strengthening risk management process for blockchain and DevOps environments. These enhancements are expected to increase the maturity level of APO12 from 3.5 to 4.1, thereby improving BankCo’s risk management, compliance, and innovation capabilities. Ultimately, the findings contribute to continuous digital innovation by aligning risk management practices with strategic performance goals and adaptive control mechanisms rooted in emerging technology principles.